Citizen Science for Nature Conservation in Hungary A Three-Dimensional Approach - Johanna Maribel Soria Aguirre; Olivér Váczi; Marianna Biró; Erika Juhász; Zoltán Soltész; Barbara Barta; Zsuzsanna Márton; Tibor Szép; Bálint Halpern; István Szentirmai; Balázs Károlyi; Alexandra Czeglédi; et al. (Citizen Science: Theory and Practice)
Nature conservation–related citizen science (NCCS) has grown rapidly worldwide in previous years. In Hungary, a few citizen science (CS) projects have been operating for years and some have only recently launched. Our aim herein is to assess the performance of eight Hungarian NCCS projects in three dimensions: a) science, b) nature conservation, and c) participants’ development. An evaluation framework was developed for the assessment. Our results show that the Common Bird Monitoring Program performed the best overall. This is also the oldest NCCS project in the country. When comparing the performance per dimension, the majority of the projects tended to have good performances in the science dimension. Most of the projects ensure data quality using different strategies. However, the need for open data and processing the project results for generating scientific publications still needs to be tackled by some NCCS initiatives. Regarding the nature conservation dimension, data generated have been mostly used in monitoring species/ecosystems, whereas data is less commonly used for conservation policy-making. It was identified that the participants’ development dimension has not received sufficient attention, and neither learning outcomes nor behavioral and attitude change has been evaluated by any projects. Our results of evaluating Hungarian NCCS initiatives in a complex way may offer insights for project managers and coordinators to identify which dimension are performing well and which areas need improvement. Also, our framework serves as a model that can be applied to current and future NCCS initiatives.